Agricultura vertical para aumentar la producción de alimentos en áreas urbanas - Castro Canales, Damari Suguey (2023)
This document discussed Vertical Agriculture to increase food production in urban areas. These particular crops are grown in different parts of Ecuador because they present irregularities that negatively impact their development. The combination of these elements encourages the adoption of sustainable agricultural techniques and has a positive impact on urban populations. The main objective of this agricultural approach is to determine the importance of vertical farming in increasing food production in urban areas. A qualitative and descriptive approach to the methodology was developed, and information was collected from up-to-date sources for the creation of this report. Websites, journals, scientific papers, online library resources, and any relevant reference materials to advance this study. Vertical farming helps to better control the growing environment, reducing the need for pesticides and fertilizers, which helps reduce the environmental impact. It was concluded that Vertical Farming in urban areas uses various techniques to grow food efficiently in limited spaces. Some of the most common techniques include stackable shelves, growing towers, green walls and hydroponic systems, it is recommended to encourage innovation and research in advanced agricultural technologies, which can have broader applications in vertical farming, improving the efficiency of the country's natural resources.